1984
DOI: 10.1113/jphysiol.1984.sp015057
|View full text |Cite
|
Sign up to set email alerts
|

Sensory‐motor processing in substantia nigra pars reticulata in conscious cats.

Abstract: SUMMARY1. Extracellular recordings were made with chronically implanted micro-electrodes from 109 substantia nigra neurones in conscious cats. Ninety-six of 109 neurones met the criteria of presumed non-dopaminergic pars reticulate (s.n.r.) neurones. Background discharge, in animals in a state of relaxed wakefulness and in the absence of overt movements, was in the range of 11-37 impulses/s, mean 19-2 impulses/s.2. The discharges of fifty-two of ninety-six neurones tested were modified by innocuous mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 45 publications
3
21
0
Order By: Relevance
“…A considerable percentage of SN cells was related to movements of the upper limb confirming results obtained in the SNc of rats (Diana et al 1989) and in the SNr of cats (Schwarz et al 1984) and monkeys (Nishino et al 1985), but in contrast to other reports , Schultz 1983). The differences may be due to the distinct experimental approach followed.…”
Section: Discussionsupporting
confidence: 89%
“…A considerable percentage of SN cells was related to movements of the upper limb confirming results obtained in the SNc of rats (Diana et al 1989) and in the SNr of cats (Schwarz et al 1984) and monkeys (Nishino et al 1985), but in contrast to other reports , Schultz 1983). The differences may be due to the distinct experimental approach followed.…”
Section: Discussionsupporting
confidence: 89%
“…Some data suggest that the DMN could also be involved in basal ganglia functions. Particularly interesting in this respect is the parallelism observed between the DMN and SN pars reticulata (SNR), a nucleus that plays an important role in motor response and in the pathophysiology of basal ganglia diseases (DeLong et al, 1983;Schwarz et al, 1984;Schultz, 1986;Schultz and Romo, 1990;Obeso et a., 1997). Both the SNR (Gonzá lez-Herná ndez and and DMN (Mugnaini and Oertel, 1985;Appell and Behan, 1990;Esclapez et al, 1993) are composed of GABAergic neurons.…”
mentioning
confidence: 97%
“…Earlier studies suggested that the CN is involved in visuomotor behavior and contributes to the control of visually guided oculomotor and skeletomotor functions (Lynd-Balta & Haber, 1994;Hikosaka, et al, 2000;Schwarz, et al, 1984;Barneoud, et al, 2000). Based on our results we can conclude that the dynamic component of the visual information is represented in two different ways in the CN.…”
Section: Visual Information Processing In the Cn Of Monkeysupporting
confidence: 49%